VOIP TECHNOLOGY SIMULATION BASED ON HYBRID FIBER COAXIAL CABLE - Suryaputra Paramita, Adi (Proceedings of KNASTIK, 2012)
This Research aims to determine how the implementation of the Hybrid FiberCoaxial (HFC) network for Voice Over Internet Protocol (VOIP), as is well-knownthat these days VOIP networks increasingly widespread use as an alternative in thefield of communication, in building a VOIP network would need an infrastructure Agood network and reliable, one important factor is the network speed andbandwidth required, in this study will be tested how the implementation of the use ofHFCs for VOIP networks, and the results of existing trials indicate that HFCprovides the smallest delay compared to another medium transmission, from theresult can be seen that at present one of the medium best transmission forimplementing a VOIP network is a Hybrid Fiber Coaxial